Tamil and Tamils: A Study of Language and Identity amongst the Indian Tamil Community in Singapore - Rajan, Rajeni (Curtin University, 2018)
This study investigated language shift in the Tamil community, a minority group in Singapore, and the maintenance of their mother tongue, Tamil as well as notions of identity amongst young Tamils. Contrary to previous studies, this study takes a stance that there is a possibility for Tamil to be a living language in Singapore, and in light of the positive attitudes and growing support observed amongst young English-educated Tamils, the declining use in Tamil may be gradually averted.